PERANCANGAN SISTEM INFORMASI PENDATAAN MURID PADA SEKOLAH DASAR NEGERI 08 SUNGAI RUMBAI SECARA KOMPUTERISASI - yuldi, epri (Jurnal Sakinah, 2019)
Data Collection system pupils in primary School aims to help the School make it easier to pupil data. Therefore, school should have student data collection system. Student data collection system was developed using the java programing language and microsoft Access the database. Sekolah Dasar Negeri 08 Sungai Rumbai still experiencing problems in the student data collection. The problem is the lock of student information system data collection, so it necessary to design a new system. To take into easy data collection. Student information system design can simplify data collection and improve the effectiveness of the school and the operator.